TINGKAT PENGETAHUAN ORANG TUA TERHADAP PENGGUNAAN ANTIBIOTIKA PADA ANAK - tansri, Suhartini; Rahmi Makmur (Jurnal Kesehatan Yamasi Makassar, 2024)
Antibiotics used for the treatment of infections. The irrational use of antibiotics can result in a significant increase in antibiotic resistance, especially infectious diseases. This study was conducted to determine the level of knowledge of antibiotic use for children in the community of Taipajawaya Hamlet, Barembeng Village, Gowa Regency. This study is an observational study with a survey method research design or quantitative method using a questionnaire. The results of the study obtained the largest correct answer = 96% which stated that the community mostly knew that information on how to use antibiotic drugs should be conveyed when handing over drugs. And the smallest number of correct answers = 63% which states that the community is less aware that all antibiotic drugs must be taken until they run out even though they feel cured. The level of knowledge of the people of Taipajawaya Hamlet, Barembeng Village, Gowa Regency towards the use of antibiotics in the sufficient category (73.6%) as many as 67 out of 91 people.